Drug prevalence and comparison interaction between numbers of patients admitted at two teaching hospitals; Quetta, Pakistan - Abdul Qadeer; Abdul Wahid; Asad Khan; Hafsa Kanwal; Muhammad Rasool (Archives of Nursing Practice and Care - Peertechz Publications, 2020)
Aim and objective: Drug-drug interaction (DDI) is of major concern in patients with complex therapeutic regimens. The study aims to assess the prevalence of DDIs in the prescriptions of patients during the hospitalization to evaluate the DDIs of drugs regarding its severity, pharmacodynamic and pharmacokinetic. Methodology: The prescribed drugs in the admission chart of 183 patients were screened for Drug-drug interaction using Mediscape interaction screening program. Drug-drug interactions have been classified on the basis of severity (contraindicated, significant, minor, major, moderate and serious). Frequency and the percentage of pairs of drugs with DDIs, number of prescribed drugs, demographics and DDIs on the basis of and Pharmacodynamics, Pharmacokinetics have been analysed. Results: The overall result shows the frequency and percentage of drug-drug interaction present in hospitalized patients, out of 183 was 125(68.3%). Majority of interactions was found on the basis pharmacokinetic DDI 108(59.0%). On the basis of severity, minor Drug-drug interaction was found dominant 91(49.7%) followed by contraindicated 19(10.4%). Conclusion: Drug-drug interaction is common among hospitalized patient's medications. My study evaluated a positive relation between prevalence of DDIs and number of drugs prescribed. Survey concluded that percentage of minor and contraindicated DDIs at admission were produced by changes of medication during hospitalization.